Capital Contribution in Industrial Property Rights to Invention Created in Startups in Vietnam - Thanh, Tran Cao (VNU Journal of Science: Policy and Management Studies, 2018)
Abstract: Capital contribution in industrial property rights to inventions created in innovative startups in Vietnam is a controversial issue. The Vietnamese laws do not have specific regulations on this issue, which is a huge barrier in seeking a common voice between the investor and the patent owner. Therefore, a specific legal corridor is required in order to promote the development of the entrepreneurial ecosystem and to help ensure the legitimate rights and interests of the stakeholders contributing to startups. This paper focuses on analyzing and clarifying the bottlenecks on capital contribution in startups, and then, recommends a number of solutions to mitigate risks for stakeholders to contribute to the  developing of the Vietnamese economy. Keywords: Capital contribution, invention, innovative startups